Cellular Therapy for Heart Failure - J. Psaltis, Peter; Schwarz, Nisha; Toledo-Flores, Deborah; J. Nicholls, Stephen (Current Cardiology Reviews, 2016)
The pathogenesis of cardiomyopathy and heart failure (HF) is underpinned by complex changes at subcellular, cellular and extracellular levels in the ventricular myocardium. For all of the gains that conventional treatments for HF have brought to mortality and morbidity, they do not adequately address the loss of cardiomyocyte numbers in the remodeling ventricle. Originally conceived to address this problem, cellular transplantation for HF has already gone through several stages of evolution over the past two decades. Various cell types and delivery routes have been implemented to positive effect in preclinical models of ischemic and nonischemic cardiomyopathy, with pleiotropic benefits observed in terms of myocardial remodeling, systolic and diastolic performance, perfusion, fibrosis, inflammation, metabolism and electrophysiology. To a large extent, these salubrious effects are now attributed to the indirect, paracrine capacity of transplanted stem cells to facilitate endogenous cardiac repair processes. Promising results have also followed in early phase human studies, although these have been relatively modest and somewhat inconsistent. This review details the preclinical and clinical evidence currently available regarding the use of pluripotent stem cells and adult-derived progenitor cells for cardiomyopathy and HF. It outlines the important lessons that have been learned to this point in time, and balances the promise of this exciting field against the key challenges and questions that still need to be addressed at all levels of research, to ensure that cell therapy realizes its full potential by adding to the armamentarium of HF management.
Keywords: mesenchymal stem cells